Recapitulation of Candidate Systemic Lupus Erythematosus-Associated Variants in Koreans - Ki-Sung Kwon; Hye-Young Cho; Yeun-Jun Chung (Genomics & Informatics)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that affects multiple organ systems. Although the etiology of SLE remains unclear, it is widely accepted that genetic factors could be involved in its pathogenesis. A number of genome-wide association studies (GWASs) have identified novel single-nucleotide polymorphisms (SNPs) associated with the risk of SLE in diverse populations. However, not all the SNP candidates identified from non-Asian populations have been validated in Koreans. In this study, we aimed to replicate the SNPs that were recently discovered in the GWAS; these SNPs have not been validated in Koreans or have only been replicated in Koreans with an insufficient sample size to conclude any association. For this, we selected five SNPs (rs1801274 in FCGR2A and rs2286672 in PLD2, rs887369 in CXorf21, rs9782955 in LYST, and rs3794060 in NADSYN1). Through the replication study with 656 cases and 622 controls, rs1801274 in FCGR2A was found to be significantly associated with SLE in Koreans (odds ratio, 1.26, 95% confidence interval, 1.06 to 1.50; p = 0.01 in allelic model). This association was also significant in two other models (dominant and recessive). The other four SNPs did not show a significant association. Our data support that FCGR polymorphisms play important roles in the susceptibility to SLE in diverse populations, including Koreans.